Experimental Analysis of Static and Dynamic Performance for Continuous Warren Truss Steel Railway Bridge in Heavy Haul Railway - Li, Yiqiang; Luo, Xianlong; Li, Yeming (Modelling and Simulation in Engineering, 2024)
Continuous Warren truss steel railway bridges are one of the main forms of railway bridges. Due to the deterioration of materials and the long-term effect of loads, the bridges will inevitably experience performance degradation, which may lead to the failure of the bridge structure to continue to operate. In order to study the mechanical properties of steel structure bridges after material deterioration and long-term loads, a continuous Warren truss steel railway bridge that has been in operation for nearly 30 years (built in 1996) is used as the research object, and a combination of field tests and finite element (FE) simulations are used to carry out research on its mechanical properties under different loads. The research results show that after nearly 30 years of operation, the steel structure bridge has local damage, but the bearing capacity still meets the requirements of heavy-duty traffic. At this stage, the corrosion of the steel structure and the damage of the bearing should be repaired in time to prevent the damage from expanding.